Strategi Pembangunan Daerah untuk Mengoptimalkan Pertumbuhan Ekonomi di Provinsi Kalimantan Tengah: Sebuah Analisis Deskriptif - Ilas, Yunanae Eka Asi (Asian Journal of Multidisciplinary Research, 2026)
This study aims to identify regional development strategies that can optimize the economic growth of Central Kalimantan Province, based on the RPJMD and RKPD documents. Using a descriptive quantitative approach, the research analyzes secondary data from BPS and Bapperida Central Kalimantan Province regarding economic growth from 2021 to 2025. The analysis results show that, although there were fluctuations in achieving economic growth targets, several development programs related to infrastructure improvement, education, and healthcare services in 2022 showed significant results. The study concludes that to achieve stable economic growth, the Central Kalimantan Provincial government needs to strengthen two priority programs: infrastructure development for roads and bridges and improvements in education and healthcare, with clear budget allocations each year.